Analisa Preferensi dan Status Sosial Terhadap Pembelian Daging Sapi Di Pasar Induk Among Tani Kota Wisata Batu - Kio, Lidia Kae; Darmawan, Hariadi; Rinanti, Rosyida Fajri; Murti, Ariani Trisna (Jurnal Ilmiah Fillia Cendekia, 2025)
The purpose of the research is to determine consumer preferences regarding the purchase decision of beef products at the Pasar Induk Among Tani Kota Wisata Batu. The variables studied consist of product quality (X1), product price (X2), and social factors (X3), as well as purchasing decisions as the variable (Y). The research was conducted from March to April 2024 at the Pasar Induk Among Tani Kota Wisata Batu, East Java Province. The type of research used is descriptive quantitative with a survey method. The sample chosen for the study consists of consumers who purchase fresh beef at the Pasar Induk Among Tani Kota Wisata Batu, totaling 80 respondents, using the accidental sampling method. The sources of research data consist of two types, namely primary data and secondary data. Primary data is obtained from direct interviews with respondents using a questionnaire, while secondary data comes from journals and reports from relevant institutions involved during the research process. The data analysis method used multiple linear regression analysis with the SPSS tool. The research results explain that consumer purchasing decisions are influenced by the attributes of meat quality. Consumer preferences in purchasing beef are influenced by several factors, one of the dominant ones being the cut of meat being bought. In addition, the social status of consumers also influences their choices when purchasing meat, where those with higher social status are more likely to choose premium quality beef or pay more attention to sustainability and ethics in selecting products. The recommendation from the research findings is that traders should provide the quality and cuts of beef that meet the needs and preferences of consumers. Service facilities and a cashless payment system need to be provided by the market management so that customers can shop comfortably. Keywords: Preferences, Attributes, Social Status, Purchase Decisions